PERBEDAAN KOHESIVITAS SUPORTER SEPAKBOLA LIGA INDONESIA DENGAN FANS CLUB TIM SEPAKBOLA EROPA - Fadhila Arde; Yanladila Yeltas Putra (Universitas Negeri Padang, 2020)
Difference in the cohesiveness of indonesian league football supporters with european football team fans club. This study aims to look at the differences in cohesiveness of Indonesian league soccer supporters with European soccer team fan clubs. The design of this study is comparative quantitative, with the study population namely Indonesian league football supporters Semen Padang (Spartacks) with the club fans of the European league's Real Madrid soccer team (Peña Real Madrid De Indonesia). The study sample numbered 136 people, with a purposive sampling technique. Data collection was carried out using a cohesiveness scale totaling 38 questions compiled based on a Likert scale. The data analysis technique used is the t-test different test analysis. The results obtained p value = 0.934 (p> 0.05), which means there is no significant group cohesiveness difference between Spartacks supporters and Peña Real Madrid De Indonesia fans club. Perbedaan kohesivitas suporter sepakbola liga indonesia dengan fans club tim sepakbola eropa. Penelitian ini bertujuan untuk melihat perbedaan kohesivitas suporter sepak bola liga Indonesia dengan fans club tim sepak bola Eropa. Desain penelitian ini adalah kuantitatif komparatif, dengan populasi penelitian yaitu suporter sepak bola liga Indonesia Semen Padang (Spartacks) dengan fans club tim sepak bola liga Eropa Real Madrid (Peña Real Madrid De Indonesia). Sampel penelitian berjumlah 136 orang, dengan teknik purposive sampling. Pengumpulan data dilakukan dengan menggunakan skala kohesivitas yang berjumlah 38 butir pertanyaan yang disusun berdasarkan skala likert. Teknik analisis data yang digunakan adalah analisis uji beda ttest. Hasil penelitian didapatkan nilai p = 0,934 (p> 0,05),yang berarti tidak terdapat perbedaan kohesivitas kelompokyang signifikan antara suporter Spartacks dan fans club Peña Real Madrid De Indonesia.